2008
DOI: 10.1017/s1355617708080338
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive models of medical decision-making capacity in patients with mild cognitive impairment

Abstract: This study investigated cognitive predictors of medical decision-making capacity (MDC) in patients with amnestic mild cognitive impairment (MCI). A total of 56 healthy controls, 60 patients with MCI, and 31 patients with mild Alzheimer's disease (AD) were administered the Capacity to Consent to Treatment Instrument (CCTI) and a neuropsychological test battery. The CCTI assesses MDC across four established treatment consent standards-S1 (expressing choice), S3 (appreciation), S4 (reasoning), and S5 (understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(117 citation statements)
references
References 49 publications
(71 reference statements)
5
112
0
Order By: Relevance
“…It is important to note, however, that there is individual variability within both PwMCI and PwD groups. Previous research on awareness in MCI in particular has emphasised that PwMCI vary considerably in levels of awareness and ability to make accurate self-appraisals in various domains [18,19,49]. The present study demonstrates that a minority of PwMCI show a pattern that is more like that of the majority of PwD, and it would be of interest to investigate whether and how this relates to the likelihood of progression to dementia.…”
Section: Discussionmentioning
confidence: 53%
“…It is important to note, however, that there is individual variability within both PwMCI and PwD groups. Previous research on awareness in MCI in particular has emphasised that PwMCI vary considerably in levels of awareness and ability to make accurate self-appraisals in various domains [18,19,49]. The present study demonstrates that a minority of PwMCI show a pattern that is more like that of the majority of PwD, and it would be of interest to investigate whether and how this relates to the likelihood of progression to dementia.…”
Section: Discussionmentioning
confidence: 53%
“…14,[20][21][22][23] Our multivariate regression analyses also illustrate the importance of specific cognitive abilities to treatment consent capacity, in particular short-term verbal memory and semantic knowledge. 13,24,25 However, the degree to which specific vs generalized cognitive impairment is related to decisional capacity in MG still remains an important empirical question. 26 We also investigated the relationships between demographic and clinical variables with performance on the CCTI standards.…”
Section: Resultsmentioning
confidence: 99%
“…8,14,17,21 The selective decline in understanding is, therefore, consistent with the cardinal amnestic deficits of patients with MCI. 4,29,30 This interpretation is supported by longitudinal studies of cognitive change in MCI that have demonstrated greater rates of decline in episodic and semantic memory relative to other cognitive abilities. 27,31 These findings provide insights into how MDC declines in MCI.…”
Section: Effect Of Conversion To Dementia On MDC Trajectorymentioning
confidence: 85%
“…As assessed using the CCTI vignette method, this standard requires comprehensive factual knowledge and understanding of the treatment situation and choices, and, accordingly, relies heavily on intact short-term verbal memory. 8,21,29 The reliance on short-term memory makes it a uniquely challenging standard for persons with AD and related dementias. 8,14,17,21 The selective decline in understanding is, therefore, consistent with the cardinal amnestic deficits of patients with MCI.…”
Section: Effect Of Conversion To Dementia On MDC Trajectorymentioning
confidence: 99%